YENİ TİYOSEMİKARBAZON LİGANDLARI İLE METAL KOMPLEKSLERİNİN SENTEZİ VEKARAKTERİZASYONU - ATEŞ, DAVUT (Fırat Üniveristesi, 2015)
Bu çalışmada öncelikle; tiyosemikarbazit ile farklı keton bileşiklerinin kondenzasyon reaksiyonu sonucunda bis(tiyosemikarbazon) ligandları sentezlenmiştir. Sentezlenen bu ligandlar; (2-(2-(2-metoksifenil)hydrazon)siklohekzan-1,3-diiliden) bis (hidrazin karboksitiyoamid) (L1), (2-(2-(3-nitrofenil)hydrazon)siklolohekzan-1,3-diiliden) bis (hidrazin karboksitiyoamid)(L2),4-(2-(-2,6-bis(2-karbamotiyonilhidrazon) siklohekziliden)hidrazinil)benzoik asit(L3), (2-(2-(4-bromofenil)hidrazon)siklohekzan-1,3-diiliden)bishidrazinkarbotiyoamit(L4)'dür. Elde edilen ligandların BiCl3, Cd(NO3)2.4H2O, HgCl2, Pb(NO3)2, SnCl2.2H2O, tuzları ile reaksiyonu sonucunda metal kompleksleri sentezlenmiştir. Sentezlenen ligand ve komplekslerin yapıları IR, 1H-NMR, 13C-NMR, elementel analiz, magnetik süsseptibilite, UV-Vis., kütle spektroskopisi (LC-MS), termogravimetrik analiz(TGA), diferansiyel termal analiz (DTA) ve Diferansiyel Taramalı kalorimetri (DSC) yöntemleri kullanılarak karakterize edilmiştir. L1 ligandının Bi(III) kompleksi için oktahedral, Hg(II), Sn(II) ve Cd(II) kompleksleri için tetrahedral, L2 ve L3 ligandlarının tüm kompleksleri tetrahedral, L4 ligandının Bi(III) kompleksi için oktahedral, Hg(II), Pb(II) ve Cd(II) kompleksleri için tetrahedral yapı önerilmiştir.

In this study; firstly, bis(thiosemicarbazone) ligands were synthesized by the condensation reaction of thiosemicarbazide and various ketone compounds. The synthesized ligands were (2-(2-(2-methoxyphenyl)hydrazono)cyclohexane-1,3-diylidene) bis(hydrazine carbothioamide)(L1), (2-(2-(3-nitrophenyl)hydrazono)cyclohexane-1,3-diylidene) bis(hydra-zinecarbothioamide) (L2), 4-(2-(-2,6-bis(2-carbamothioylhydrazono) cyclohexylidene) hydrazinyl)benzoic acid (L3), and (2-(2-(4-bromophenyl) hydrazono) cyclohexane-1,3-diylidene) bis(hydrazinecarbothioamide) (L4). The metal complexes were synthesized by the reaction of obtained ligands (L1, L2, L3 and L4) with BiCl3, Cd(NO3)2.4H2O, HgCl2, Pb(NO3)2, SnCl2.2H2O salts. The structures of synthesized ligands and their complexes were characterized by using IR, 1H-NMR spectra,13C-NMR spectra, Elemental analysis, Magnetic susceptibility, UV-Vis., Mass Spectrum (LC-MS), Thermogravimetry analysis(TGA), Differential thermal analysis (DTA) and Differantial Scanning Calorimetry techniques. Octahedral geometry was suggested for the Bi(III) complex of L1, whereas tetrahedral geometry were suggested for the Hg(II), Sn(II), Cd(II) complexes. The structures all of the L2 complexes and complexes of the L3 were tetrahedral . Octahedral geometry was suggested for the Bi(III) complex of L4, whereas tetrahedral geometry were suggested for the Hg(II), Pb(II), Cd(II) complexes.
Synthesis and characterization of novel thiosemicarbazone ligands and their metal complexes
Keywords: Kimya